2012
DOI: 10.1371/journal.pone.0034160
|View full text |Cite
|
Sign up to set email alerts
|

Highly Pathogenic Influenza A(H5N1) Virus Survival in Complex Artificial Aquatic Biotopes

Abstract: BackgroundVery little is known regarding the persistence of Highly Pathogenic Avian Influenza (HPAI) H5N1 viruses in aquatic environments in tropical countries, although environmental materials have been suggested to play a role as reservoirs and sources of transmission for H5N1 viruses.Methodology/Principal FindingsThe survival of HPAI H5N1 viruses in experimental aquatic biotopes (water, mud, aquatic flora and fauna) relevant to field conditions in Cambodia was investigated. Artificial aquatic biotopes, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 33 publications
3
26
3
Order By: Relevance
“…The interplay between host (reservoir birds) and viral factors could have promoted the survival of the quasispecies populations found in this study in their natural habitat while the cell-based systems could not (Horm et al, 2012).…”
Section: Discussionmentioning
confidence: 92%
“…The interplay between host (reservoir birds) and viral factors could have promoted the survival of the quasispecies populations found in this study in their natural habitat while the cell-based systems could not (Horm et al, 2012).…”
Section: Discussionmentioning
confidence: 92%
“…Aquatic environments inhabited by AIV reservoir species (i.e., waterfowl) are complex, and persistence of AIV is influenced by a combination of abiotic factors, including pH, temperature, and salinity (7,37), and biotic factors, including zooplankton, bivalves, fish, amphibians, and vegetation (21). Daphnia spp.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, zebra mussels (Dreissena polymorpha) maintained detectable amounts of viable AIV in their tissue for up to 16 days postexposure (19), and freshwater clams acted as bioconcentrators for AIV, highlighting their potential use as sentinels in AIV surveillance (20). Based on a study of H5N1 persistence in simulated complex aquatic habitats, Horm et al (21) detected infectious virus in bivalve tissue only shortly after exposure and suggested that bivalves and other aquatic fauna were passive carriers of AIV. In the first assessment of the effects of filter-feeding zooplankton on AIV persistence, Abbas et al (22) exposed Daphnia magna to AIV-dosed water and found detectable levels of virus associated with Daphnia tissue for up to 6 days postexposure.…”
mentioning
confidence: 99%
“…Recent discoveries highlight the importance of the Hh signaling pathway in prostate growth regulation [12,48] and Hh signaling pathway inhibitors therefore would be promising agents for prostate cancer therapy [12]. However, major issues with current Hedgehog pathway inhibitors include rapid acquired resistance, severe side effects and potential developmental toxicities to use in children [49]. Furthermore, most of Hh antagonists target Smo receptor and little target the signaling components down-stream of Smo, such as fused homolog (Sufu) or GLI [50,51].…”
Section: Discussionmentioning
confidence: 99%